2019
DOI: 10.1039/c9cc02556a
|View full text |Cite
|
Sign up to set email alerts
|

A new class of electrolytes based on magnesium bis(diisopropyl)amide for magnesium–sulfur batteries

Abstract: A new class of electrolytes for Mg–S batteries prepared by a facile in situ reaction of magnesium bis(diisopropyl)amide (MBA) with AlCl3, which show reasonable ionic conductivity and relatively high anodic stability on stainless steel, close to 100% Mg deposition–dissolution efficiency and high cycling reversibility and compatibility with the S cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…In Mg–S batteries, the choice of the current collector has also a great impact on the electrochemical behavior particularly in the case of halogen‐containing corrosive electrolytes, the nature of the electroactive cathode materials and the dissolution of polysulfides during cycling . The currently reported commercial metal‐based current collectors include aluminum foil, stainless‐steel (SS) foil, carbon‐coated aluminum foil, copper, and the anticorrosion alloy Inconel 625 . While Cu is generally considered unstable against chloride‐containing electrolytes, Zeng et al recently reported that a sulfur cathode is compatible with the traditional APC electrolyte using copper as current collector below 1.7 V versus Mg/Mg 2+ .…”
Section: Cathode Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Mg–S batteries, the choice of the current collector has also a great impact on the electrochemical behavior particularly in the case of halogen‐containing corrosive electrolytes, the nature of the electroactive cathode materials and the dissolution of polysulfides during cycling . The currently reported commercial metal‐based current collectors include aluminum foil, stainless‐steel (SS) foil, carbon‐coated aluminum foil, copper, and the anticorrosion alloy Inconel 625 . While Cu is generally considered unstable against chloride‐containing electrolytes, Zeng et al recently reported that a sulfur cathode is compatible with the traditional APC electrolyte using copper as current collector below 1.7 V versus Mg/Mg 2+ .…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Also, the TGA results of the cathode with a stainless‐steel current collector suggest a reaction of sulfur with the nucleophilic electrolyte as evidenced of the large weight loss of sulfur in the cathode after cycling. Due to the unique advantages of the Cu current collector, it was also applied in combination with other halogenated electrolytes including the organic magnesium boron‐based (OMBB) electrolyte, the boron‐centered base magnesium (BCM) electrolyte, the magnesium bis(diisopropylamide) (MBA) electrolyte and a trifluoromethanesulfonate‐based electrolyte …”
Section: Cathode Materialsmentioning
confidence: 99%
See 3 more Smart Citations